2021
DOI: 10.1002/mame.202000805
|View full text |Cite
|
Sign up to set email alerts
|

Production of Green Star/Linear PLA Blends by Extrusion and Injection Molding: Tailoring Rheological and Mechanical Performances of Conventional PLA

Abstract: In this work, bio‐based products composed of blends of a star‐shaped poly(d,l‐lactide) (star‐PDLLA) and a conventional linear poly(l‐lactide) (linear‐PLLA) are produced by typical large‐scale manufacturing techniques for thermoplastic blends. In the first case, the two polymers are blended through melt extrusion, producing pellets that are subsequently compression‐molded into the final bio‐based polymer films. Alternatively, the star/linear poly(lactide) (PLA) materials are developed by direct blending through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…The gaps between the agglomerated particles and rHDPE in compression molded composites are clearly observed in Figure 4 a,c. Similar results reported impregnation problem in compression molded hybrid composites attributed to the difficulty of high viscosity resins in diffusing into fiber bundles and subsequently their agglomeration (cluster) in highly viscous matrices [ 27 , 33 ]. High filler/matrix interaction may also explain the higher mechanical properties of injection molded composites due to more effective stress transfer and better interfacial quality.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The gaps between the agglomerated particles and rHDPE in compression molded composites are clearly observed in Figure 4 a,c. Similar results reported impregnation problem in compression molded hybrid composites attributed to the difficulty of high viscosity resins in diffusing into fiber bundles and subsequently their agglomeration (cluster) in highly viscous matrices [ 27 , 33 ]. High filler/matrix interaction may also explain the higher mechanical properties of injection molded composites due to more effective stress transfer and better interfacial quality.…”
Section: Resultssupporting
confidence: 73%
“…This can be attributed to the orientation of polymer chains during IM. In fact, direct injection of the specimens into the dumbbell-shaped mold induced chain orientation along the flow direction resulting in improved tensile properties along the longitudinal direction (anisotropy) [ 33 ]. Moreover, better distribution and dispersion of the fiber occurs due to a second melt-mixing step inside the injection molding screw barrel [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, 30CF-INJ has 111% higher tensile strength and 94% higher tensile modulus but 27% lower elongation at break than 30CF-COM. This is ascribed to the secondary melt-mixing step in injection, as well as the orientation of the fibers and polymer chains during injection molding, as reported in the literature [30,31]. Similar observations were obtained from SEM images (Figure 7), indicating that the fibers are mainly oriented perpendicular to the cross-section in injection-molded samples, while the fiber orientation is predominantly random, displaying more entanglements in compression-molded samples.…”
Section: Mechanical Propertiessupporting
confidence: 87%
“…The M n of unprocessed PLA (69.3 kDa) decreased to 48.2 kDa during IM, and a further decrease was observed during IM and SSE to a M n of 42.9 kDa. A similar study was performed by Scoponi et al [93], where unprocessed PLA was compared with PLA that was processed via IM, TSE, and both co-rotating twin-screw extrusion and compression molding (TSE + CM). It was observed that the M n of unprocessed PLA (74.1 kDa) decreased to 52.8 kDa after IM, 39.2 kDa after TSE, and 22.5 kDa after TSE + CM.…”
Section: Influence Of Processing Techniquementioning
confidence: 93%